The Existence of The Sun Goes Down Band in Mojokerto City on the Local Community - Yedija Purba (Universitas Negeri Surabaya, 2026)
This article discusses the existence of the band The Sun Goes Down (TSGD) in Mojokerto. This study aims to reveal the influence of TSGD on mass movements and communities, so that the industry in this small city becomes more conducive thanks to the band's existence. In analysing this issue, the researcher uses the theory of existence as outlined by Christian (2016), which includes three approaches: the relationship between existence and transcendent matters; existence as a philosophy that underlies truth and gives meaning to life; and existence as testable through thought patterns and actions. The study shows that TSGD has successfully maintained its presence in Mojokerto through various music performances. The band also evokes nostalgia among young people of the 2000s and contributes to communities beyond music, such as at thrifting festivals. In addition, TSGD has had a positive impact on major event promoters in Mojokerto by serving as guest stars at music events, thereby reviving young people's interest in the city's major events.